An Introduction to Computational Physics/ Tao Pang - Pang, Tao
Bibliography: p.369 - 380; Contents: Introduction; Approximation of a function; Numerical calculus; Ordinary differential equations; Numerical methods for matrices; Spectral analysis; Partial differential equations; Molecular dynamics simulations; Modeling continuous systems; Monte Carlo simulations; Genetic algorithm and programming; Numerical renormalization.; First published in print format 2006